Studi Hadis Tentang Banyak Anak Kaitannya Dengan Banyak Rezeki - Arofah, Siti (SHAHIH (Jurnal Ilmu Kewahyuan), 2024)
In the past and now we often hear that "many children, lots of fortune" has become a culture in Indonesia. Having children is a gift in itself for parents, therefore the existence of children is considered very important because they are the successors of offspring and also assets for the family. Through cultural communication, the assumption "many children, lots of fortune" can change a person's personality so that it is ingrained in a person. or it could be said that this assumption has been internalized within a person. The type of research used in this research is library research. Where data collection was obtained from researching books related to this discussion, then analyzed using the takhrij method, itibar sanad criticism and matan criticism as well as using the ma'ani al Hadith approach to the meaning of Hadith. Based on research conducted by the author, it was found that the Sanad and Matan Hadith were condemned by Hasan, so that they could be used as evidence. So it can be determined that the Matan Hadith narrated by Abu Daud above is Hasan because there is no syuzuz and illat in the Matan Hadith. Based on research conducted by the author, it was found that the Sanad and Matan Hadith were condemned by Hasan, so that they could be used as evidence. So it can be determined that the Matan Hadith narrated by Abu Daud above is Hasan because there is no syuzuz and illat in the Matan Hadith